2017
DOI: 10.4172/2329-6836.1000292
|View full text |Cite
|
Sign up to set email alerts
|

A Short Review on Ethnomedicinal Uses and Phytochemistry of Silybum marianum

Abstract: Herbs have been used permanently as the major source of medicine. Medicinal plants are important by secondary metabolites such as Silymarin, it is a mixture of flavonoids. Silybum marianum is a safe herb, rare reactions were reported if the dosage is high. There are medical confirmations for anticarcinogenic and hepatoprotective activities of Milk thistle. Silybum marianum is used vigorously in cirrhosis, prostate, skin and breast cancer, cervical cells and kidney ailments. This review is about the Phytochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Milk thistle or Silybum marianum (L.) Gaertn. is a common herbal medicine species used around the world with wide ethnomedicinal usage and good clinical support [ 131 ].…”
Section: Main Textmentioning
confidence: 99%
“…Milk thistle or Silybum marianum (L.) Gaertn. is a common herbal medicine species used around the world with wide ethnomedicinal usage and good clinical support [ 131 ].…”
Section: Main Textmentioning
confidence: 99%
“…The plant grows wildly in various habitats and is also cultivated in Europe, Asia, and North America [2]. This is due to its medicinal importance and sometimes as a food supplement [3][4]. On the other hand, it has been reported that the plant extract inhibits metal corrosion [5][6][7].…”
Section: Introductionmentioning
confidence: 99%